Policing Policy: Change to ICE Detainer Policy - (:unkn) unknown (My University, 2014)
In response to the Miranda-Olivares v. Clackamas County [OR] case, the Thurston County Sheriff's Office/Corrections Bureau will no longer book and/or enter into the jail management system (ATIMS), ICE 48 Hour Detainer Requests.
Keywords: Sanctuary Policies; Miranda-Olivares v. Clackamas County